EFEKTIVITAS LAYANAN BIMBINGAN DAN KONSELING DI SMAN 6 KARAWANG - Annisa, Siti; Cahyani, Sri Bulan; Amani, Suci Jaoharoh; Nabila, Sarah Julia; Putra, Tri Maulana; Farida, Nur Aini (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to evaluate the effectiveness of Guidance and Counseling (BK) services at SMAN 6 Karawang, highlighting the challenges arising from the limited number of BK teachers. A descriptive quantitative method was employed, involving surveys with students and interviews with BK teachers. The results indicate that with only two BK teachers serving hundreds of students, individual attention becomes less optimal. Students with serious issues are prioritized, while others tend to be overlooked. Consequently, services such as individual counseling, group counseling, and home visits are less effective. The study also found that a lack of socialization results in students being unaware of the available BK programs. Recommendations include increasing the number of BK teachers, providing specialized training, and enhancing program socialization to better support students' holistic development.